Phosphorylation of bacterial-type phosphoenolpyruvate carboxylase at Ser425 provides a further tier of enzyme control in developing castor oil seeds - O'Leary, Brendan; Rao, Srinath K; Plaxton, William C (Biochemical journal, 2011)
PEPC [PEP (phosphoenolpyruvate) carboxylase] is a tightly controlled anaplerotic enzyme situated at a pivotal branch point of plant carbohydrate metabolism. Two distinct oligomeric PEPC classes were discovered in developing COS (castor oil seeds). Class-1 PEPC is a typical homotetramer of 107 kDa PTPC (plant-type PEPC) subunits, whereas the novel 910-kDa Class-2 PEPC hetero-octamer arises from a tight interaction between Class-1 PEPC and 118 kDa BTPC (bacterial-type PEPC) subunits. Mass spectrometric analysis of immunopurified COS BTPC indicated that it is subject to in vivo proline-directed phosphorylation at Ser425. We show that immunoblots probed with phosphorylation site-specific antibodies demonstrated that Ser425 phosphorylation is promoted during COS development, becoming maximal at stage IX (maturation phase) or in response to depodding. Kinetic analyses of a recombinant, chimaeric Class-2 PEPC containing phosphomimetic BTPC mutant subunits (S425D) indicated that Ser425 phosphorylation results in significant BTPC inhibition by: (i) increasing its Km(PEP) 3-fold, (ii) reducing its I50 (L-malate and L-aspartate) values by 4.5- and 2.5-fold respectively, while (iii) decreasing its activity within the physiological pH range. The developmental pattern and kinetic influence of Ser425 BTPC phosphorylation is very distinct from the in vivo phosphorylation/activation of COS Class-1 PEPC's PTPC subunits at Ser11. Collectively, the results establish that BTPC's phospho-Ser425 content depends upon COS developmental and physiological status and that Ser425 phosphorylation attenuates the catalytic activity of BTPC subunits within a Class-2 PEPC complex. To the best of our knowledge, this study provides the first evidence for protein phosphorylation as a mechanism for the in vivo control of vascular plant BTPC activity.